Site-dependent selectivity in oxidation reactions on single Pt nanoparticles. Issue 34 (20th March 2020) - Dery, Shahar; Kim, Suhong; Feferman, Daniel; Mehlman, Hillel; Toste, F. Dean; Gross, Elad
Abstract : Site-dependent selectivity in oxidation reactions on Pt nanoparticles was identified by conducting IR nanospectroscopy measurements while using allyl-functionalized N-heterocyclic carbenes (allyl-NHCs) as probe molecules. Abstract : Site-dependent selectivity in oxidation reactions on Pt nanoparticles was identified by conducting IR nanospectroscopy measurements while using allyl-functionalized N-heterocyclic carbenes (allyl-NHCs) as probe molecules. Following exposure to oxidizing conditions the allyl groups in NHCs that were located on the center of Pt nanoparticles were oxidized to hydroxyl while those located on the nanoparticle's periphery were oxidized into carboxylic acid. The superior reactivity on the periphery of the nanoparticles was correlated to higher density of low coordinated atoms on these surface sites.